Neurology of foreign language aptitude - Biedroń, Adriana (Studies in Second Language Learning and Teaching, 2015)
This state-of-the art paper focuses on the poorly explored issue of foreign language aptitude, attempting to present the latest developments in this field and reconceptualizations of the construct from the perspective of neuroscience. In accordance with this goal, it first discusses general directions in neurolinguistic research on foreign language aptitude, starting with the earliest attempts to define the neurological substrate for talent, sources of difficulties in the neurolinguistic research on foreign language aptitude and modern research methods. This is followed by the discussion of the research on the phonology of foreign language aptitude with emphasis on functional and structural studies as well as their consequences for the knowledge of the concept. The subsequent section presents the studies which focus on lexical and morphosyntactic aspects of foreign language aptitude. The paper ends with a discussion of the limitations of contemporary research, the future directions of such research and selec ed methodological issues.